2019
DOI: 10.1038/s41598-019-49446-w
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome provides insights into the growth behaviour and resveratrol and trans-stilbenes biosynthesis in Dactylorhiza hatagirea - An endangered alpine terrestrial orchid of western Himalaya

Abstract: This is the first report on de novo transcriptome of Dactylorhiza hatagirea, a critically-endangered, terrestrial orchid of alpine Himalayas. The plant is acclaimed for medicinal properties but little is known about its secondary-metabolites profile or cues regulating their biosynthesis. De novo transcriptome analysis was therefore, undertaken to gain basic understanding on these aspects, while circumventing the acute limitation of plant material availability. 65,384 transcripts and finally, 37,371 unigenes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Over the years, the market value of crude drugs obtained from the plant has shown an increasing trend which has led to the expansion of its market across different Indian states [13,[47][48][49]. The huge demand in the pharmaceutical sector has driven a flourishing trade of around USD 71,583 [50]. Kala [51] reported that the annual demand for D. hatagirea is approximately 5000 tons, due its use in both traditional as well as modern medicine.…”
Section: Distribution Trade and Consumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the years, the market value of crude drugs obtained from the plant has shown an increasing trend which has led to the expansion of its market across different Indian states [13,[47][48][49]. The huge demand in the pharmaceutical sector has driven a flourishing trade of around USD 71,583 [50]. Kala [51] reported that the annual demand for D. hatagirea is approximately 5000 tons, due its use in both traditional as well as modern medicine.…”
Section: Distribution Trade and Consumptionmentioning
confidence: 99%
“…The antioxidant property of compounds obtained from the plant finds its use in the treatment of different human diseases. Indole alkaloids, phenolics (stilbene, e.g., resveratrol), and saponins along with ascorbic acid, phyllo-and naphthloquinones, glucomannan, and carotenoids [50] [80] (Table 3). plant finds its use in the treatment of different human diseases.…”
Section: Bioactive Compounds Of D Hatagireamentioning
confidence: 99%
See 2 more Smart Citations
“…However, its use in D. hatagirea has not yet been documented. De novo transcriptome analysis of D. hatagirea revealed the presence of differentially expressed genes governing various metabolic pathways and stress tolerance (Dhiman et al, 2019).There exists a vast opportunity in transcriptomic of D. hatagirea, which can be used to reveal various aspects of its uses and values in human life.…”
Section: Genetic Diversitymentioning
confidence: 99%